Risk of cardiovascular events after initiation of long-acting bronchodilators in patients with chronic obstructive lung disease: A population-based study. (30th September 2016) - Aljaafareh, Almotasembellah; Valle, Jose Ruben; Lin, Yu-Li; Kuo, Yong-Fang; Sharma, Gulshan
Objectives: Long-acting bronchodilators are mainstay treatment for moderate to severe chronic obstructive pulmonary disease. A growing body of evidence indicates an increased risk of cardiovascular events upon initiation of these medications. We hypothesize that this risk is higher in patients with chronic obstructive pulmonary disease who had a preexisting cardiovascular disease regardless of receipt of any cardiovascular medication. Methods: A retrospective cohort of patients with a diagnosis of chronic obstructive pulmonary disease based on two outpatient visits or one inpatient visit for chronic obstructive pulmonary disease (International Classification of Diseases, 9th Edition, Clinical Modification codes 491.x, 492.x, 496) in any year between 2001 and 2012 from a commercial insurance database. We then selected those initiating long-acting bronchodilator treatments between April 2001 and September 2012. Each patient had a 1 year look back period to determine history of cardiovascular disease or cardiovascular disease treatment from the time of first prescription of long-acting beta agonist, long-acting muscarinic antagonist, or long-acting beta agonist combined with inhaled corticosteroids. Patients were followed for 90 days for hospitalizations or emergency department visits for cardiovascular event. The cohort was divided into four groups based on the presence of cardiovascular disease (including ischemic heart disease, hypertension, ischemic stroke, heart failure, tachyarrhythmias and artery disease based on International Classification of Diseases, 9th Edition, Clinical Modification codes) and cardiovascular disease treatment defined as acetylsalicylic acid, beta blockers, angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, antiplatelet, anticoagulants, calcium channel blockers, nitrate, digoxin, diuretics, antiarrhythmics or statins. Odds of emergency department visit or hospitalization in the 90 days after prescription were examined using multivariable logistic regression models. Results: Of 61, 651 eligible patients, 36, 755 (59.6%) had cardiovascular disease and were on cardiovascular disease treatment (Group 1), 7250 (11.8%) had cardiovascular disease without cardiovascular disease treatment (Group 2), 4715 (7.7%) had no cardiovascular disease but had cardiovascular disease treatment (Group 3) and 12, 931 (21%) had no cardiovascular disease and no treatment (Group 4). In these four groups, the unadjusted risk of emergency department visit or hospitalization for cardiovascular disease within 90 days of initiation was 5.45%, 2.95%, 1.55% and 0.96%, respectively. In multivariable analysis, the adjusted odds ratio with 95% confidence interval of emergency department visit/hospitalization for each of the first three groups to those with no cardiovascular disease and no treatment were 3.50 (95% confidence interval, 2.89–4.24), 2.15 (95% confidence interval, 1.71–2.70) and 1.36 (95% confidence interval, 1.01–1.82), respectively. Conclusion: The risk of cardiovascular events after initiation of long-acting bronchodilators is highest in patients with baseline cardiovascular disease and on cardiovascular disease medications. Clinicians should be cautious while prescribing these medications in patients with preexisting cardiovascular disease.